1991
DOI: 10.1021/jf00005a020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis before and after cooking processes of a trace chlorpyrifos spiked in polished rice

Abstract: Polished rice grains were fortified with 500 p p b of chlorpyrifos. T h e fortified residues were analyzed by gas chromatography with a nitrogen-phosphorus detector or a Hall detector. Chlorpyrifos and its breakdown product 3,5,6-trichloro-2-pyridinol were recovered from fortified rice grains in the levels of 456 and 3.4 ppb, respectively. Washing rice grains with water removed approximately 60% of the chlorpyrifos residues. Fortified chlorpyrifos was found in cooked rice at a level of 130 ppb, which was appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…The results are also differed to those of Krol et al (2000) who found that rinsing fruits and vegetables with tap water for 15-30 s produced significant reductions in residue levels of malathion, iprodione and other pesticides but not of chlorpyrifos. On the other hand, washing rice grains with water removed approximately 60 % of the chlorpyrifos residues (Lee et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The results are also differed to those of Krol et al (2000) who found that rinsing fruits and vegetables with tap water for 15-30 s produced significant reductions in residue levels of malathion, iprodione and other pesticides but not of chlorpyrifos. On the other hand, washing rice grains with water removed approximately 60 % of the chlorpyrifos residues (Lee et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The level of EDB in cooked rice appeared to be related to subtle differences in cooking techniques. Lee et al (1991) reported that washing of rice grains spiked with chlorpyriphos (500 ppb) removed approximately 60% of residues. However, it was found to be 30% of original quantity in cooked rice.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…Washing rice grains with water removed approximately 60% of the chlorpyrifos residues (Lee, Mourer, & Shibamoto, 1991).…”
Section: Washingmentioning
confidence: 99%